Perspectivas de sujeitos envolvidos em movimentos sociais sobre a hanseníase e seu controle em uma área endêmica - Fabiana Nascimento Lopes (2014)
Despite investments in developing new technologies for the treatment, diagnosis and the adoption of new strategies for disease control in Brazil, Leprosy remains a public health problem in the country. Almenara, a municipal district located in the Jequitinhonha Valley - MG is a priority for leprosy control for presenting a detection rate considered high by the Ministry of Health. The countys healthservices have presented difficulties for carrying out the actions proposed by the National Leprosy Control Programme, since a study has shown that the population, even living with the disease for years, has difficulty to understand important disease aspects that can influence the early detection of new cases. Health counsellors and community leaders are important social agents of the county who can contribute to the health service in leprosy control, for possessing a large representativeness within communities and/or groups they serve. In order to involve Almenaras social agents in leprosy control, the study aimed to assess leprosy as a public health problem from the health advisors and community leaders perspective. This paper uses a qualitative research methodology conducted with ten health counsellors and seven community leaders from Almenaracounty where data collection has been done under a semi-structured interview technique. Data analysis has been carried out based on a qualitative content analysis as proposed by Laville and Dione (1999), which allowed the data to be analysed into two different categories. Data analysis has been performed according to the analytical approaches in this study. The results have pointed out that social agents identify the spots with sensitivityloss as the disease characteristics, but they mistake reactions and physical disabilities with the disease signs. The health service has had difficulty to perform early diagnosis of the disease, which has contributed to a scenario where leprosy is seen as a disease that has no cure due to appearance of reactions. How leprosy is passed on to others is the main source of doubts regarding the disease, and it has been linked to fear, prejudice and stigma towards people who carry the disease. The delays and difficulties in diagnosis as well as the use of posters and flyers to raise community awareness were the main weaknesses pointed out by the participants. Community leaders and health counsellors do not recognise and have never participated in the efforts to control leprosy in the county, what indicates a difficulty faced by the health service to foster a social movement in fighting the disease. For leprosy no longer be a health problem in Almenara county, it is necessary that people treat it as a priority since only the community has the power to set the disease as a priority to health community managers.